X-Ray Diffraction and Zn K -Edge XANES Studies of Perovskite Ferroelectric PZT-PZN Powders Derived from Zn 2Nb34O87 Precursor - Amonpattaratkit P. (2017)
© 2016 Taylor & Francis Group, LLC. An approach to synthesize perovskite ferroelectric 0.9Pb(Zr0.4 4 Ti 0.56 )O 3 -0.1Pb(Zn0.3 3 Nb 0.67 )O 3 or 0.9PZT-0.1PZN powders with a modified mixed-oxide synthetic route via a combination of the perovskite PZT phase stabilizer and the novel intermediate phase of Zn 2 Nb 34 O 87 B-site has been developed. Phase formation, morphology, particle size, chemical composition and oxidation state of the products were investigated as a function of calcination temperatures. It has been found that the pyrochlore phase of Pb 3 Nb 4 O1 3 tends to form together with the perovskite phase of PZT-PZN, depending on calcination temperatures. It is seen that optimization of calcination condition can lead to a 100% yield of PZT-PZN in a tetragonal perovskite phase. The tetragonality factor, degree of agglomeration, crystallite size and average particle size tend to increase with the calcination temperatures. In addition, the synchrotron X-ray absorption near edge structure (XANES) analysis showed the oxidation state of Zn 2+ atoms for all condition of 0.9PZT-0.1PZN powders.